PEMANFAATAN METIL ESTER JARAK PAGAR MENJADI SURFAKTAN MES UNTUK APLIKASI SEBAGAI OIL WELL STIMULATION AGENT - Erliza Hambali; Dadang Rukmana; Riztiara Nurfitri (Jurnal Ilmu Pertanian Indonesia, 2012)
Year by year, globally the production of petroleum decreases but its demand increases. The world will get the energy crisis including Indonesia if that condition happens continously. Because of that, Indonesia starts to develop IOR (improved oil recovery) method for their oil fields.  IOR method is an improvement of the secondary phase in which the oil recovery is expected to increase oil production.  One method of IOR is chemical injection with surfactant for injection.  Surfactant is dissolved with injection water and injected to reservoir.  Generally, surfactant of petroleum sulphonates is used for oil recovery.  Due to the weaknesses of petroleum suphonates such as not resistant in high salinity and high hardness water, therefore it triggers to get surfactant substitute like MES (methyl ester sulphonates) that is synthesized by bio-oil from Jatropha curcas L.  The study was aimed to know the performance of MES surfactant formula from jatropha oil for IOR in fluid sample of oil field and synthetic sandstone core.  The best condition from this research was surfactant 0.2 PV with the soaking time of 12 hours. This formula gave the highest of  incremental total oil recovery 61%. The number were resulted from 48% waterflooding and 13% surfactant injection.